MODEL FUNGSI TRANSFER MULTI INPUT DALAM PERAMALAN PENERIMAAN PAJAK HOTEL KOTA MALANG TAHUN 2019 - Alma Perwitasari; Nur Atikah (UNIVERSITAS NEGERI MALANG, 2020)
A transfer function is one of the models contained in the time series. The multi-input transfer function is used to establish a simple model derived from the relationship between input and output series. The transfer function model will be applied to the forecasting of hotel tax revenue (Y) into an output series with the input series variables affected by the number of sold rooms (X^a), the number of staying guests (X^b), and the average of the guest’s staying time (X^c). The purpose of this study is to anticipate the failure of the realization of the hotel tax revenue target in Malang City and to determine the results of the next forecasting. The result of this study is the multi-input transfer function, Y_t = Y_(t-1) + 0.0052294*X^b_(t-8) + 573.32180*X^c_t - 0.0052294*X^b_(t-9) - 573.32180*X^c_(t-1) + 1.18967*a_t. Based on this function, the forecasting nearly coincides with the actual data indicated by the graph of forecasting result nearly coincides with the graph of the actual data. Thus, this multi-input transfer function could be suggested to be used in forecasting Malang City hotel tax revenues from January 2019 to May 2019.